2020
DOI: 10.1016/j.cca.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Hock-a-loogie saliva as a diagnostic specimen for SARS-CoV-2 by a PCR-based assay: A diagnostic validity study

Abstract: Highlights The detection rate of hock-a-loogie saliva was higher than nasopharyngeal swabs. Hock-a-loogie saliva sample had a higher viral load than throat swab. Hock-a-loogie saliva sampling for SARS-CoV-2 detection is reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 16 publications
4
26
2
1
Order By: Relevance
“…The results demonstrated that saliva specimens showed higher positivity rate than NPS and OPS and supported the findings of previous studies (Fan et al, 2020;Sakanashi et al, 2021). It may be attributed to high expression of ACE2 in the alveoli, which is the receptor of SARS-CoV-2, making a large amount of virus accumulate in the lower respiratory tract (Fan et al, 2020;Wan et al, 2020). After a deep cough, the virus is flushed out with air pressure and wrapped in sputum or saliva, thereby making saliva to contain a higher viral load and easier to be detected positive (Fan et al, 2020;Wan et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results demonstrated that saliva specimens showed higher positivity rate than NPS and OPS and supported the findings of previous studies (Fan et al, 2020;Sakanashi et al, 2021). It may be attributed to high expression of ACE2 in the alveoli, which is the receptor of SARS-CoV-2, making a large amount of virus accumulate in the lower respiratory tract (Fan et al, 2020;Wan et al, 2020). After a deep cough, the virus is flushed out with air pressure and wrapped in sputum or saliva, thereby making saliva to contain a higher viral load and easier to be detected positive (Fan et al, 2020;Wan et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, four methods were used for simultaneous testing, and the gold standard for diagnosis was any positive result of the four methods. The results demonstrated that saliva specimens showed higher positivity rate than NPS and OPS and supported the findings of previous studies ( Fan et al., 2020 ; To et al., 2020 ; Sakanashi et al., 2021 ). It may be attributed to high expression of ACE2 in the alveoli, which is the receptor of SARS-CoV-2, making a large amount of virus accumulate in the lower respiratory tract ( Fan et al., 2020 ; Wan et al., 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The complex and specific expression pattern of immunity proteins, such as IgA, IgM and IgG, can last up to 3 months leading to the detectable signals both in serum and in saliva 10 . Specifically, saliva represents a reliable biofluid for the detection being involved in the first phases of infection with the persistent presence of biological molecules directly involved in the SARS-CoV-2 presence 36 , 37 . Clinical data collected from COV- patients, revealed periods of negativization between 8 and 90 days explaining the persistence in the Raman signals of differences when compared with CTRL and COV+ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, we and others have shown that saliva can serve as an alternative upper respiratory tract specimen type for SARS-CoV-2 detection. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 This is significant as saliva offers a number of advantages over nasopharyngeal swabs when considering the aforementioned criteria for mass testing efforts. Specifically, saliva does not require a certified swab and collection receptacle and does not necessarily have to be obtained by a skilled healthcare provider, both of which increase diagnostic-associated costs.…”
Section: Introductionmentioning
confidence: 99%